The Experience Society How Consumer Capitalism Reinvented Itself - Miles, Steven (Pluto Press, 2020)
Airbnb, gaming, escape rooms, major sporting events: contemporary capitalism no longer demands we merely consume things, but that we buy experiences. This book is concerned with the social, cultural and personal implications of this shift.The technologically-driven world we live in is no closer to securing the utopian ideal of a leisure society. Instead, the pursuit of leisure is often an attempt to escape our everyday existence. Exploring examples including sport, architecture, travel and social media, Steven Miles investigates how consumer culture has colonised 'experiences', revealing the ideological and psycho-social tensions at the heart of the 'experience society'.The first critical analysis of the experience economy by a UK sociologist sheds light on capitalism's ever more sophisticated infiltration of the everyday.